A comparison of autologous serum, plasma, and whole blood for intradermal autoreactivity testing in patients with chronic spontaneous urticarial: a cross-sectional study - Ismail, Rasimah; Jamil, Adawiyah; Md. Nor, Norazirah; F. Bakhtiar, Mohammed (Saudi Society of Dermatology and Dermatologic Surgery, 2022)
Background: Autologous serum (ASST) and plasma (APST) skin testing confirm autoreactivity in chronic spontaneous urticaria (CSU). Whole blood autohemotherapy has been used. Plasma and even whole blood may be used instead of serum with relatively quicker preparation and cheaper method especially using the latter in centers with limited resources. Purpose: The purpose of the study is to determine if similar intradermal skin reactions can be observed when using either serum, plasma, or whole blood in autologous skin tests and to determine factors associated with positive tests and wheal diameter. Methods: We performed a cross-sectional study of chronic urticaria patients in a dermatology clinic. Tests were performed according to EAACI/GA2 LEN Task Force recommendations. Urticaria Activity Score over 7 days (UAS7) was assessed. Statistical analyses included Chi-square, Mann–Whitney U, Spearman’s, and Wilcoxon rank tests. Results: Twenty-six (77%) females and 8 (24%) males mean age 34 (26–42) years participated. ASST, APST and autologous whole blood for skin testing (AWBST) positivity rates were 24%, 29% and 27%, respectively (P = 0.86). 13 (38%) had at least 1 positive test; all tests were negative in 21 (62%). All tests were positive in 7 (21%), 3 (23%) were positive APST alone, 2 (15%) AWBST, 1 (8%) ASST. Pretest UAS7 was higher with those with test positive (P = 0.04). Test results were unaffected by age, gender, disease duration, atopy, anti‑nuclear antibody, and thyroid status. Wheal diameter correlated with thyroid-stimulating hormone (P = 0.04). Conclusion: Autoreactivity rates were similar with ASST, APST,and AWBST. Positive tests were associated with severe CSU. Autologous whole blood may be a simpler and less costly alternative to plasma and serum for autoreactivity skin testing in patients with chronic urticaria.